ChemInform Abstract: Lancolides [A (Ia), B (IIa), C (Ib), D (IIb)], Antiplatelet Aggregation Nortriterpenoids with Tricyclo[6.3.0.02, 11]undecane‐Bridged System from Schisandra lancifolia. Issue 9 (4th March 2014) - Shi, Yi‐Ming; Wang, Xin‐Bo; Li, Xiao‐Nian; Luo, Xiao; Shen, Zi‐Ying; Wang, Yi‐Ping; Xiao, Wei‐Lie; Sun, Han‐Dong
Abstract Lancolides A (Ia) and D (IIb) show specific antiplatelet aggregation induced by platelet‐activating factor (PAF).